2013
DOI: 10.5850/jksct.2013.37.7.852
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Trypsin on Chitosan Nonwoven Using Glutaraldehyde

Abstract: We investigate the immobilization of trypsin on chitosan nonwoven using glutaraldehyde (GA). The conditions for trypsin on chitosan nonwoven and GA cross-linking were optimized depending on different conditions. The order of GA cross-linking was determined by the activity of immobilized trypsin. The characteristics of chitosan nonwoven were examined by Fourier-transform infrared (FT-IR) and surface morphology analyses (SEM). Results showed that the optimal treatment conditions for trypsin on chitosan nonwoven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Chitosan nonwoven was pre-activated with glutaraldehyde at the optimal treatment conditions according to previous work [36]. A previous study indicated glutaraldehyde pretreatment conditions concerning pH, glutaraldehyde concentration, and crosslinking time for chitosan nonwovens to increase the activity of immobilized enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…Chitosan nonwoven was pre-activated with glutaraldehyde at the optimal treatment conditions according to previous work [36]. A previous study indicated glutaraldehyde pretreatment conditions concerning pH, glutaraldehyde concentration, and crosslinking time for chitosan nonwovens to increase the activity of immobilized enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…Optimization of the crosslinking conditions using GA on PET BSA Figure 5 shows the optimization of crosslinking conditions using GA with various pH values (a), GA concentrations (b) and crosslinking times (c). To optimize the pH of the crosslinking solution, the crosslinking time using GA was controlled to 120 min (Figure 5 (a)), according to Kim et al 23 At pH values lower than 8.0, the reaction between the aldehyde groups in GA and amino groups in enzymes decreased during the crosslinking process. 24 However, the relative activity increased at pH 8.0 or more, consistent with the results of a previous study 25 that reported that increasing the pH to obtain alkaline conditions promotes GA crosslinking and increases the amount of immobilized enzyme in a linear manner.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the crosslinking time was shortened to 90 min in contrast to the 120 min used in a previous study. 23 Thus, the conditions for GA crosslinking on the PET BSA fabric were optimized to pH 10.0, 3% (v/v) GA, and 90 min crosslinking time. Hereafter, PET GA has been used to refer to samples crosslinked with GA under optimal conditions on PET BSA .…”
Section: Resultsmentioning
confidence: 99%
“…The amount of immobilized trypsin was determined by measuring absorbance at 410 nm with L-BAPNA as the substrate. 7,22,23 After the immobilization process, the recovered activity of the immobilized trypsin was calculated from the following equation: 7,24–28 where Ra is the activity recovery of the immobilized enzyme (%), A i is the activity of the immobilized enzyme (U), and A f is the activity of the same amount of free enzyme in solution as that immobilized on the support (U).…”
Section: Methodsmentioning
confidence: 99%
“…The activity of immobilized trypsin was measured each time using the method described above. 22,23,34…”
Section: Stability Assessmentmentioning
confidence: 99%